The impact of maternal body mass index on maternal and perinatal outcome - Bhushan, Nishu; Kumar, Surinder; Kumar, Dinesh; Khajuria, Reema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The incidence of obesity has increased to pandemic proportions over the last 20 years. Obesity is a chronic illness which is associated with metabolic disease, nutritional deficiency, musculoskeletal complications and carcinomas. The aim of the study was to evaluate and compare the maternal and perinatal outcome in patients with BMI 20-24.9 kg/m2 (normal), with BMI 25-29.9 kg/m2 (overweight) and with BMI >30 kg/m2 (obese). Methods: This cross-sectional study was conducted on 300 singleton pregnant women with gestational age>37 weeks with cephalic presentation. The selected women were categorized into three groups of 100 each according to their BMI: Category I included normal women (BMI 20-24.9 kg/m2), Category II included overweight women (BMI 25-29.9 kg/m2) and Category III included obese women (BMI >30 kg/m2). Results: There was increased incidence of antepartum complications in obese women. The difference in the occurrence of pre-eclampsia among the three categories was statistically significant (p=0.001). Similarly, more obese women had eclampsia (5%) and gestational diabetes mellitus (6%) as compared to overweight and normal women and the difference was statistically significant in both these complications (p=0.02 for each). The risk of induction of labour was highest in obese women and so was the incidence of caesarean and instrumental deliveries and the difference was statistically significant. The difference in the onset of labour as well as mode of delivery among the three categories was statistically significant (p<0.05). In perinatal outcomes, the difference in mean birth weight of the babies among three categories was statistically significant (p<0.0001). The difference in incidence of low birth weight (<2.5 kg) as well as macrosomia (>4 kg) among babies of three BMI categories was statistically significant (p<0.05). The difference in the incidence of NICU admissions was statistically significant (p=0.02). Conclusions: Obesity is an independent risk factor for adverse pregnancy outcomes and hence preventable steps should be taken for reducing the maternal and perinatal morbidity and mortality.